Cannabis use patterns, motivations, and reasons for abstinence in pregnancy - Blair, Lisa M.; Shukla, Meghna; Kurzer, Julie A. M. J.; Schilt-Solberg, Marvin; Strickland, Biyyiah A.; Akter, Salma; Fend, Dennette; Hamann, Kimberly; Ashford, Kristin (Frontiers in Psychiatry, 2025)
IntroductionPrenatal use of cannabis, and co-use of tobacco, has escalated rapidly despite well-documented risks to pregnancies and offspring. The purpose of the present study was to examine relationships between prenatal cannabis use, motivations for use, reasons for abstinence, co-use with tobacco and nicotine, and quit attempts among a cohort of persons who used cannabis in their current pregnancy. MethodsPersons who used cannabis at least once during their current pregnancy were recruited from prenatal clinics and surveyed. Descriptive statistics and logistic regression (n = 59) were used to determine differences between those who had continued (past 30-day) use of cannabis compared to those who did not. ResultsThe data reveal that motivations for use and reasons for abstinence of cannabis are complex, with many participants indicating past, unsuccessful attempts to quit. Current cannabis use (past 30 days) was reported by 61% of participants, with 54% of those endorsing daily use and 85% endorsing use at least 15 of the past 30 days. Those who endorsed five or more motivations for use were over 10 times as likely to have recent cannabis use. DiscussionThis study highlights major research gaps and discusses clinical and policy implications of the findings and of perinatal cannabis.